From Compliance to Competitive Advantage: Driving Sustainability Transformation in Indonesia’s Manufacturing Sector - Donasius Sagita Nanlohy; Tiolina Evi (Journal of Educational Management Research, 2026)
This study aims to develop an integrative framework explaining how PESTEL dynamics and dynamic capabilities drive sustainability transformation in Indonesia’s manufacturing sector. Sustainability has become a strategic imperative due to escalating environmental crises and increasing global pressure on industries to align economic growth with ecological boundaries. However, a persistent gap remains between macro-level sustainability policies and their practical implementation, particularly in emerging economies characterized by institutional complexity and resource constraints. This research adopts a conceptual design using systematic literature scoping from major databases between 2021 and 2025 to ensure contemporary relevance. The analysis employs an inductive–deductive approach through theory mapping, construct refinement, and integration to synthesize a coherent framework. The findings reveal that PESTEL functions as an interconnected system rather than isolated factors, creating multidimensional pressures on firms. Organizational responses are heterogeneous, shaped by internal interpretive capacities rather than external forces alone. Dynamic capability acts as a strategic mediator through sensing, seizing, and transforming processes that enable firms to convert constraints into opportunities. Sustainability paradoxes further complicate decision-making and influence strategic outcomes. This study contributes theoretically by bridging macro and micro perspectives while offering practical guidance for managers and policymakers. Future research should empirically test the framework across sectors.